HAK DAN KEWAJIBAN NEGARA PEMILIKI INSTALASI LEPAS PANTAI TERHADAPNAVIGASI INTERNASIONALMENURUTHUKUMINTERNASIONAL - Hefni, Hanna Adistyana (UI Scholars Hub, 2021)
Along with the times, the types and methods of exploration and exploitation of the seaare also experiencing developments, such as oil and gas drilling offshore and the construction of offshore installations to smooth the process of oil andgas exploitation and production. The emergence of other objects besides ships in the waters certainlybecomes a problem for international navigation activities which have long been the activities of nations since ancient times. Therefore this paper discusses the rights and obligations of the countries that have offshore installations to international navigation according to international law. The method used in this paper is a normative research method. Furthermore the results of this paper find that in aneffort to implement these rights and obligations States have adopted a 500-meter safety zone policy around offshoreinstallations. So far no cases of violations of international navigation have been found as a result of the presence of theseoffshore installations.